2011
DOI: 10.1117/1.3575168
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz sensing in corneal tissues

Abstract: This work introduces the potential application of terahertz (THz) sensing to the field of ophthalmology, where it is uniquely suited due to its nonionizing photon energy and high sensitivity to water content. Reflective THz imaging and spectrometry data are reported on ex-vivo porcine corneas prepared with uniform water concentrations using polyethylene glycol (PEG) solutions. At 79% water concentration by mass, the measured reflectivity of the cornea was 20.4%, 14.7%, 11.7%, 9.6%, and 7.4% at 0.2, 0.4, 0.6, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 34 publications
5
63
0
2
Order By: Relevance
“…9 Additionally, our previous work has shown that THz imaging is extremely sensitive to changes in the local water concentration in skin (and has been demonstrated in a number of phantom characterization targets). 3,5,7 Therefore, burn wounds are ideally suited for THz imaging applications as they cover a relatively large area of skin and are known to provoke an extreme postinjury response. This response is apparent in the image Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 Additionally, our previous work has shown that THz imaging is extremely sensitive to changes in the local water concentration in skin (and has been demonstrated in a number of phantom characterization targets). 3,5,7 Therefore, burn wounds are ideally suited for THz imaging applications as they cover a relatively large area of skin and are known to provoke an extreme postinjury response. This response is apparent in the image Fig.…”
mentioning
confidence: 99%
“…The last decade has witnessed significant proliferation of THz devices, technologies, and applications with considerable attention given to medical imaging and diagnostics. 1 THz medical imaging has been applied to the detection and spatial mapping of skin cancer, 2 corneal hydration, 3 and breast cancer. 4 Recently, THz imaging has been successfully applied to the imaging of burn wounds on ex vivo pig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Difference in the water content of the tissue has been recently proposed as the main basis for many biomedical and biological applications of terahertz radiation. [16][17][18] Pickwell et al furthermore showed that a double Debye dielectric relaxation model can be used to describe the terahertz response of healthy human skin, 19,20 which is very similar to the model often used for polar liquids. 21 Pulsed-terahertz emissions have also been used to image and delineate basal cell carcinoma [22][23][24] and human breast cancer tumor margins, 25,26 based on the differences in the water content of the cancerous tumor versus healthy tissue.…”
Section: Terahertz Modality For Characterization Of Burn Woundsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] THz images of thermal burns were first demonstrated on ex vivo chicken skin burned using an argon ion laser by Mittleman et al 9 It has been demonstrated again in ex vivo porcine skin burns induced using a thermal brand. 10 THz imaging of chemical burns was demonstrated on 33% sulfuric acid burns on ex vivo porcine skin by Bennett et al 6 This study achieved time-resolved imaging which showed the severity of the burn progressing over a 2-h time course. THz evaluation of water content was also used to distinguish cirrhosis in liver tissue extracted from Sprague-Dawley (SD) rats.…”
Section: Introductionmentioning
confidence: 99%